Analisa Kekuatan Sambungan Las Tig Pada Pengujian Tarik dan Kekerasan Plat Stainless Steel Setelah Proses Pemanasan Dengan Suhu 6000c di Tempering Dengan Minyak Rem dan Air Bercampur Garam - Ahmadin ahmadin (MAJALAH TEKNIK SIMES, 2021)
Abstract Heat treatment, heat treatment and rapid cooling to obtain the changing properties of carbon steel, metal or guides. One of the treatment methods is the tempering process. This process is carried out at a temperature of 6000C for 30 minutes then tempering with brake fluid and air mixed with salt. The results of the average tensile stress without heat treatment obtained yield stress ?y = (58.14) kgf / mm2, ultimate stress ?u = (71.2) kgf / mm2, breaking stress ?f = (68.13) kgf / mm2, Result The average tensile stress of 6000C heat treatment treated with brake fluid obtained yield stress ?y = (37.89) kgf / mm2, ultimate stress ?u = (48.33) kgf / mm2, breaking stress ?f = (43.58) kgf / mm2and the results of the average tensile stress of 6000C heat treatment which is tempered with salt water, the yield stress is obtained ?y = (31.14) kgf / mm2, ultimate stress ?u = (45.86) kgf / mm2, breaking stress ?f = (36, 8) kgf / mm2. For the hardness tester the chase results that the average values for the area ofthe parent metal, HAZ metal and weld m etal. Untreated specimens for the parent metal area obtained 58.6 HRB, for the HAZ metal area obtained 51.1 HRB and for the weld metal area obtained 53 HRB, specimens that received 6000C treatment with brake fluid for the parent metal area obtained 57.8 HRB, for the HAZ metal area obtained 50.4 HRB and for the metal area obtained 58.6 HRB and specimens that received 6000C treatment with 800 gr air mixed with salt for the parent metal area obtained 56.8 HRB, for the HAZ metal area obtained 49.4 HRB and for the weld metal area obtained 49.8 HRB. From the results of this study it can be concluded that the untreated specimens have the best tensile strength and hardness level compared to the welded joints of specimens that received heat treatment at a temperature of 6000C. While the specimens that received heat treatment at a temperature of 6000C were tempered with air mixed with 800gr of salt, the tensile strength and hardness level decreased more than the specimens that received heat treatment at 6000C which were tempered with brake fluid.